Visual culture projects in basic education: Other ways of seeing the school culture - Sardelich, Maria Emilia (2015)
This paper presents one research of Grupo de Pesquisa em Ensino das Ar- tes Visuais (GPEAV), Universidade Feder- al da Paraíba (UFPB), on Visual Culture projects in Basic Education in contrast to the concepts of school and curriculum, in the Resolution CNE / CEB n . 4/2010. The exploratory research has analyzed published projects in Visual Culture Book Collection, organized by the Universi- dade Federal de Santa Maria(UFSM). The study concludes that the Visual Culture projects have extended the boundaries of the   curricular component of art, due to the pedagogical position that favors whom sees, the subjectivity , opened to other interpretations and ways of seeing and thinking.